1987
DOI: 10.1002/em.2860090602
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Mutagenicity tests: III. Results from the testing of 255 chemicals

Abstract: The results and data from the testing of 255 chemicals for mutagenicity in Salmonella are presented. All chemicals were tested under code using a preincubation modification of the Salmonella/microsome test in the absence of exogenous metabolic activation and in the presence of liver S-9 from Aroclor-induced male Sprague-Dawley rats and Syrian hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
113
1
7

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(122 citation statements)
references
References 6 publications
1
113
1
7
Order By: Relevance
“…The toxic effects of methacrylonitrile have also been attributed to the in vivo release of cyanide and depletion of glutathione (Hartung 1982). There are few mutagenicity studies on methacrylonitrile; however, the available evidence indicates that the chemical is not genotoxic (Knaap et al 1985;NTP 2000;Zeiger et al 1987;Zimmering et al 1989).…”
mentioning
confidence: 95%
“…The toxic effects of methacrylonitrile have also been attributed to the in vivo release of cyanide and depletion of glutathione (Hartung 1982). There are few mutagenicity studies on methacrylonitrile; however, the available evidence indicates that the chemical is not genotoxic (Knaap et al 1985;NTP 2000;Zeiger et al 1987;Zimmering et al 1989).…”
mentioning
confidence: 95%
“…[21] These compounds were chosen because of the presence of a rhodanine heterocyclic core, which is biocompatible, non-mutagenic, [22] and has a drug-like profile. Inspired by these results, we wanted to explore whether these compounds will also inhibit amyloid fibril formation of IAPP which has a completely different amino acid sequence but shares a similar fibrillar morphology with the tau aggregate.…”
mentioning
confidence: 99%
“…These results show a higher sensitivity of fish cells when they are compared with other biological material tested, and thus, for example, Zeiger et al (1987) using the Ames test demonstrated that TCCA does not induce gene mutations. Hammond et al (1986) reported that there was no evidence of cyanurate-induced chromosomal aberrations chlorinated isocyanurates; and in chromosomal aberration tests in vitro, clastogenicity or polyploidy in CHL/IU cells was not induced in the absence or presence of an exogenous metabolic activation system (MHW 1997).…”
Section: Discussionmentioning
confidence: 84%